Islamic Social Finance Innovation: Sharia Legal Analysis of Waqf Crowdfunding - Melda Luciani; Moelki Fahmi Ardliansyah; Husnul Fatarib (Al Dzahab, 2026)
Purpose: This study aims to analyze the implementation of waqf crowdfunding on the Kitabisa.com platform from a Sharia law perspective based on DSN–MUI Fatwa No. 117/2018, as well as to identify the challenges in optimizing digital waqf as an instrument of social funding. Design/Methodology/Approach: This study employs a qualitative approach using a case study of the Kitabisa.com platform through the analysis of documents, regulations, and fatwas, applying a descriptive-analytical method. Findings: The findings indicate that waqf fundraising through Kitabisa.com is generally in accordance with Sharia principles, as reflected in the use of cash waqf, collaboration with authorized nazhir, and the allocation of investment returns to welfare-related sectors. However, several challenges remain, including low levels of waqf literacy among the public, potential risks associated with Sharia-based investments, and the need for standardized transparency in reporting. Research Implications: The optimization of waqf crowdfunding requires clearer regulatory frameworks, increased public literacy regarding waqf, effective risk management mechanisms, equitable fund distribution, and transparent reporting systems to strengthen public trust.